The role of financial analysis in risk management of entrepreneurial small and medium-sized enterprises: A case study of DJI Innovation Technology Co., LTD - Wen, Jiayi (Transactions on Economics, Business and Management Research, 2024)
As an important tool of risk management, financial analysis can help enterprises to identify, evaluate, prevent and monitor financial risks in a timely manner, optimize management processes, and ensure the steady development of enterprises. This paper aims to explore the role of financial analysis in the risk management. Through in-depth analysis of the characteristics of small and medium-sized enterprises, combined with financial analysis methods, this paper puts forward a set of risk management framework suitable for small and medium-sized enterprises. The results show that effective financial analysis can significantly improve the risk management level of enterprises and provide guarantee for the steady development of enterprises.